2004
DOI: 10.1524/ract.92.4.355.35607
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic tracer studies of chemical behavior of rare earth elements in environmental and biological sciences

Abstract: Rare earth elements (REE), a group of elements with atomic numbers from 57 to 71, have been widely applied in recent years not only in industry but also in agriculture, forestry, animal husbandry and medicine. Numerous anthropogenic activities make REE to easily enter the environment and finally the human body via the food chain. Therefore, detailed studies on chemical behavior of these metals in environmental and biological systems are imperative. Isotopic tracer method is especially suited to such studies an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…In the domain of industrial applications, the γ-emitter 169 Yb (39 d half-life) has been used in sealed sources for industrial applications, for substitution of 192 Ir sources applied in conventional non-destructive testing (NDT) projectors, providing better quality of the radiographic pattern [39]. The longer lived 173,174 Lu are used as ra-dioactive tracers in different processes [40,41] and the 172 Lu( 172 Yb) decay is used for investigation ion implantation in semiconductors by using PAC technique [42], and for radiotracer studies of oil pipeline flow rates, refinery column residence times, and the performance of a coal liquefaction pilot plant [43]. Deuteron induced reactions on ytterbium however, are not the most favorable reactions for production of some of these radionuclides as for instance 169 Yb, 177 Lu and 175 Yb can be produced much more economically at reactors via (n,γ ) reactions.…”
Section: Integral Yieldsmentioning
confidence: 99%
“…In the domain of industrial applications, the γ-emitter 169 Yb (39 d half-life) has been used in sealed sources for industrial applications, for substitution of 192 Ir sources applied in conventional non-destructive testing (NDT) projectors, providing better quality of the radiographic pattern [39]. The longer lived 173,174 Lu are used as ra-dioactive tracers in different processes [40,41] and the 172 Lu( 172 Yb) decay is used for investigation ion implantation in semiconductors by using PAC technique [42], and for radiotracer studies of oil pipeline flow rates, refinery column residence times, and the performance of a coal liquefaction pilot plant [43]. Deuteron induced reactions on ytterbium however, are not the most favorable reactions for production of some of these radionuclides as for instance 169 Yb, 177 Lu and 175 Yb can be produced much more economically at reactors via (n,γ ) reactions.…”
Section: Integral Yieldsmentioning
confidence: 99%
“…Depending on the chemical form and stability of the complexes, their distribution in organs or tissues (e.g. liver, bone) as well as their urinary excretion was different (Zhang and Chai 2004;Rosoff et al 1963). A recent human study demonstrated the influence of the chemical form of ruthenium (Ru) on its kinetics in plasma.…”
Section: Resultsmentioning
confidence: 99%
“…It can be alloyed with stainless steel to improve some of its mechanical properties [1], used as a doping agent in fibre optic cables [2], in making lasers [3], in ceramic industry [4], in dentistry [5], and used for the production of medically and technologically important radionuclides [6][7][8][9][10]. Therefore, an accurate knowledge of activation cross-sections of ytterbium isotopes is indispensable for various practical applications in science and technology.…”
Section: Introductionmentioning
confidence: 99%
“…The radionuclide 173 Lu (T 1/2 = 1.37 y) was proposed to be utilized as a radiation source for crack detectors in c defectoscopes instead of 75 Se [23]. The long-lived 174 Lu is also used as a radioactive tracer in various process streams [9].…”
Section: Introductionmentioning
confidence: 99%